La Geografía en la encrucijada - Higueras Arnal, Antonio (Geographicalia, 2016)
Geography is a discipline which has always been in a state of crisis due to the fact that its aim, the land surface, is not exclusive since there are many other disciplines which study the land surface. Since the time of Humboldt geography has been considered a discipline of synthesis which studies everything that exists at the same time in an area of land surface. However, since the second world war many geographers have abandoned this concept of geograply with the excuse that "a science, for everything" can not exist. Until then they said, geography had been a descriptive discipline which had had to became as cientific and explicative one. To do so it had had to change its theoretical concepts,methods and analytical techniques. All of this led to a great crisis in modern geography because the effects of the geographical revolution have not been as efficient as they seemed at first. The way out of the crisis is perhaps in the partial return to its origins: geography can continue being a discipline of synthesis if the geographical facts are considered as systerns.